ANALISIS GERAK JUMP SHOOT TERHADAP TINGKAT KEBERHASILAN POINT DI TIM BOLA BASKET UNIT KEGIATAN MAHASISWA - Fachru Falah Adina; Saichudin Saichudin; Rias Gesang Kinanti (Universitas Negeri Malang, 2017)
Abstract: Jump shoot is a shooting movement with a jump to avoid the opponent. This study aims to analyze the motion of jump shoot from the angle aspect of the arm, foot angle, throwing angle, maximum height, and ball speed. This research uses quantitative-qualitative research design using descriptive analysis. Data collection is done by ten objects with each object given the opportunity to do the experiment three times and analyzed with dartfish software. The results of the research carried out on average in the ball category entered the arm angle 92.35 º, ball speed 2.36 m / s, foot angle 163.85 º, maximum height 5.20 m, and 37.4 º throw angle. In the five instruments that greatly affect the success of the point if not paid attention then the ball motion will not be appropriate direction.Keywords: analysis, jump shoot, Dartfish.